INFORMED CONSENT DALAM PELAYANAN KESEHATAN DI RUMAH SAKIT (ANALISIS PUTUSAN KASASI MAHKAMAH AGUNG NOMOR 3004 K/PDT/2014): INFORMED CONSENT DALAM PELAYANAN KESEHATAN DI RUMAH SAKIT (ANALISIS PUTUSAN KASASI MAHKAMAH AGUNG NOMOR 3004 K/PDT/2014) - Doni; Yeti Kurniati; Thariq Muslim; Dhea Alfie; Ery Firsanti; Hodijatussolihah (Jurnal Media Justitia Nusantara, 2025)
“Informed consent in healthcare services at hospitals is a crucial aspect that must be understood and implemented by medical professionals. The Supreme Court Decision Number 3004 K/Pdt/2014 highlights the importance of informed consent prior to medical actions being taken. This analysis employs a normative legal research method to evaluate the application of informed consent based on existing regulations. Informed consent requires doctors to provide clear information regarding the diagnosis, purpose of the action, risks, and available alternatives. This aims to enable patients to make conscious and informed decisions. In the ruling, the judge emphasized that merely obtaining a patient's signature on a document is insufficient; adequate explanations must be provided so that patients fully understand the consequences of medical actions. This decision also underscores the legal responsibilities of medical professionals and hospitals in cases of negligence in providing information. In emergency situations, doctors may act based on presumed consent but must still provide information once the emergency is resolved. Thus, the application of the informed consent principle not only protects patient rights but also provides legal protection for doctors, fostering transparency in the relationship between patients and healthcare providers”.